The legal personality of natural entities: a paradigm shift? - García de Enterría Ramos, Andrea (Journal of the Basque Parliament, 2023)
The recent approval of Law 19/2022, of September 30, for the recognition of legal personhood to the Mar Menor lagoon and its basin, forces us to reflect on the existing environmental protection and its possible insufficiency. This situation has led to the emergence of a position, increasingly widespread in comparative law, advocates for the advancement in the defense of the environment through techniques as innovative as that applied in the Mar Menor, through the recognition of legal personhood to particular ecosystems, considering whether this figure will be extended to protect other threatened areas or if, on the contrary, it will be an isolated case. After the Constitutional Court has declared the admissibility of the appeal for lodged against the Act, the judgment is pending.